ELECTRON MICROSCOPIC ANALYSIS OF ENLARGED CELLS DERIVED FROM RED SEA BREAM IRIDOVIRUS (RSIV)-INFECTED CULTURED GRUNT FIN (GF) CELLS - Ketut Mahardika (Indonesian Aquaculture Journal, 2013)
Red sea bream iridovirus (RSIV) has been known to induce cellular enlargement as cytophatic effect (CPE) in cultured cell line. In the present study, grunt fin (GF) cells were treated with RSIV. After advanced of CPE, the cellular enlargement were harvested, processed and analysis under electron microscopy. Electron microscopy revealed inclusion body bearing cells (IBCs), and enlarged and rounded cells allowing virus propagation within the intracytoplasmic virus assembly site (VAS). Most were enlarged cells. These enlarged cells were divided into three cells types. Enlarged cells of the type I, which contained many mature virions were numerous in the number rather than enlarged cells of type II which contained many immature viral particles and enlarged cells of type III which allowed assembly of a few virions. These results determined that basic ultrastructure feature of RSIV infected GF cells is formation of IBCs and cells containing a few, many mature and immature viral particles within VAS.